Double the trouble: giant proteins with dual kinase activity in the heart - Grogan, Alyssa (Biophys Rev, 2020)
Obscurin and its homolog, striated muscle preferentially expressed gene (SPEG), constitute a unique group of proteins abundantly expressed in striated muscles that contain two tandemly arranged MLCK-like kinases. The physiological significance of the dual kinase motifs is largely understudied; however, a collection of recent studies characterizing their binding interactions, putative targets, and disease-linked mutations have begun to shed light on their potential roles in muscle pathophysiology. Specifically, obscurin kinase 1 is proposed to regulate cardiomyocyte adhesion via phosphorylating N-cadherin, whereas SPEG kinases 1 and 2 regulate Ca(2+) cycling by phosphorylating junctophilin-2 and the sarcoendoplasmic Ca(2+) ATPase 2 (SERCA2). Herein, we review what is currently known regarding the potential substrates, physiological roles, and disease associations of obscurin and SPEG tandem kinase domains and provide future directions that have yet to be investigated.